Successful aging at work and age-related contextual information influence simulated performance appraisal decisions - Hanscom, Madison E., author; Cleveland, Jeanette, advisor; Fisher, Gwenith, committee member; Murphy, Kevin, committee member; Shore, Lynn, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2017)
As the age of the workforce increases, it is important to understand that information other than objective job performance influences the performance evaluation process and decisions. Performance information is used as a basis for multiple organizational decisions, thus it is critical to understand how alternative age concepts may influence these important work outcomes. Much research has been conducted using chronological age to examine these linkages although few studies have incorporated more recent measures of aging perceptions. Using a within subjects 2 x 3 x 2 experimental vignette methodology across three samples, the present study examined the influence of successful aging at work (successful and not successful), the age type of the job (young type of job, age neutral, and old), and performance pattern (younger or older) on performance ratings, promotion and layoff decisions, recommendations for upgrade training, bonus money administration, and organizational resource investments. Results showed significant main effects for successful aging at work on performance-based outcomes. Less consistent relationships were found with job type and performance pattern. These results are discussed in relation to previous research on age-performance relationships, theoretical support, as well as implications for future research.